Religious Beliefs and Teacher’s Identity: An Autoethnography of A Muslim English Teacher - Maesaroh, Dwi Titi (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Teacher’s religious identity or personal faith is significantly associated with their professional identity and teaching practice in the classroom. The purpose of this study is to narrate a Muslim English teacher’s views on how religious beliefs influence the teacher’s identity and practices in teaching English. Employing autoethnography research design, I explored my experience and perspectives since I was an English learner, then a student-teacher, an English teacher at an Islamic school, and a lecturer at a college using personal experience narration. In this article, I acknowledge that my perspectives about my professional identity as an English teacher are shaped locally and globally, influenced by religious beliefs, experiences, education, and formal and informal interaction with colleagues around me. This study gives insight into the influences of a Muslim English teacher’s religious beliefs on identity as an English teacher and practices in teaching English.